1978
DOI: 10.1073/pnas.75.10.5181
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of fatty acid cyclooxygenase from human aorta to acetylation by aspirin.

Abstract: The rate of acetylation of fatty acid cyclooxygenase (prostaglandin synthase, EC 1.14.99.1) by [acetyl-3H-aspirin was measured in microsomes from human aortas and coronary arteries and intact and disrupted human platelets. We also measured the inhibition by aspirin of prostacyclin generation from exogenous arachidonic acid in shredded human aorta. Cyclooxygenase in human aorta and coronary artery microsomes is approximately 1/250th as sensitive to aspirin as enzyme in intact platelets, and 1/60th as sensitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

1979
1979
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(38 citation statements)
references
References 16 publications
0
38
0
Order By: Relevance
“…The previous observation that aspirin is less effective in sonicated than in intact platelets [10] also is likely to be related to the formation of PGG 2 and 12-HPETE from the arachidonic acid released on cell disruption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous observation that aspirin is less effective in sonicated than in intact platelets [10] also is likely to be related to the formation of PGG 2 and 12-HPETE from the arachidonic acid released on cell disruption.…”
Section: Discussionmentioning
confidence: 99%
“…The relative ineffectiveness of aspirin as an anti-inflammatory drug is mirrored at the cellular level by the demonstration that aspirin is 166 times more potent in inhibiting PGHS activity in the platelet than in the J774.2 macrophage cell line [8], leading to consideration that the action of aspirin might be selective for the PGHS-1 isoform. However, the potency of inhibition of PGHS-1 by aspirin ex vivo observed in normal platelets is lost in platelets of patients after coronary artery bypass grafting [9], and PGHS-1 from platelet homogenates is poorly acetylated by aspirin [10], suggesting differences in acetylation that can not be attributed to isoform selectivity. Collectively, these observations reflect considerable variability in acetylation of the PGHSs by aspirin, a variability that implies a mechanistic basis for regulating the action of the drug.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies have demonstrated that: a single dose of 80 mg of aspirin reduces the activity of prostaglandin synthetase by 85% and a dose of 300 mg completely abolishes it (Burch et al, 1978); a single dose of 2 mg/kg is enough to inhibit completely the generation of MDA, measured 2 h after oral ingestion, while between 3 and 3.5 mg/kg is needed to inhibit ADP-, adrenaline-or collagen-induced aggregation (Masotti, Poggesi, Galanti, Abbate & Neri Serneri, 1979); and finally that a dose of 100 mg of aspirin reduces TXB2 release by more than 90% in serum 2 h after oral administration and by 100% after 3 to 4 h (Patrono, Ciabattoni, Pinca, Pugliese Castrucci, De Salvo, Satta & Peskar, 1980). These last authors also found that a clear dose-effect on the generation of TXB2 can only be obtained with doses below 22mg/kg of aspirin.…”
Section: Aspirin Haemostasis and Thrombosismentioning
confidence: 99%
“…[10][11][12][13][14][15][16] In this respect, studies with long-term aspirin should look not only at normal individuals but also at specific populations for whom a beneficial effect of antiplatelet therapy has been advocated (e.g., diabetics). Such individuals are significantly different from normal individuals in that they have an increased platelet turnover and decreased platelet life span,17 which may have important effects on the ability of the platelets and the vessel to recover from the effects of aspirin.…”
mentioning
confidence: 99%